Ambiguidade e dilaceração: Simone de Beauvoir, leitora de Hegel e Kojève (Revista Eletrônica Estudos Hegelianos, 2022)
Although Simone de Beauvoir’s characterization of womanhood not as a mere given but as a construction has clear emancipatory implications for the denaturalization of female subordination, she has subsequently been criticized for an overemphasis on transcendence at the expense of immanence, which would culminate in a masculinist ideal of human emancipation based on control over one’s own body and the natural world. This critique, however, merely reverses the signs, preserving the distinction between immanence and transcendence as an unmediated, seemingly unbridgeable schism. We suggest in this article that a more productive approach to the relationship between immanence and transcendence – between sex and gender, nature and spirit, object and subject – is to be found in Beauvoir’s own writings. To this end, we turn to the essay Ethics of Ambiguity (1947) to propose a distinction between ambiguity and dilaceration that, albeit less explicitly, is also present in The Second Sex (1949), which is attested in the reading of Hegel’s philosophy presented in the book. While, on the one hand, Beauvoir was inspired by Alexandre Kojève’s reading of the so-called “master-slave dialectic” to propose an agonistic conception of subjectivity formation, on the other hand she distances herself from key assumptions of the Kojèvian interpretation by refusing an ontological dualism between nature and spirit and adopting a strong understanding of intersubjectivity. In this double theoretical movement, which can be characterized as a rapprochement with respect to Hegel, Beauvoir then lays the groundwork for a non-masculinist ideal of women’s emancipation.